CYSP-HS: A new version of the CYSP directional neutron spectrometer with increased sensitivity. (December 2018) - Bedogni, R.; Gómez-Ros, J.M.; Pola, A.; Treccani, M.; Costa, M.
Abstract: CSYP (CYlindrical SPectrometer) is a directional neutron spectrometer based on a single moderator embedding multiple thermal neutron detectors. Similarly to Bonner Spheres, CYSP responds from thermal up to GeV neutrons and the spectrum is obtained via few-channel unfolding methods. CYSP has the shape of a polyethylene cylinder with diameter 50 cm and height 65 cm. Owing on a thick collimator and on a specifically designed shielding structure, the internal detectors only respond to neutrons coming from a known direction. Internal thermal neutron detectors are one-cm 2 6 LiF-covered silicon diodes. Un upgraded version of CYPS was developed to work in low intensity applications, such as cosmic field measurements. It is called CYSP-HS (High-Sensitivity) and is equipped with large area 6 LiF-covered silicon diodes (LATND, Large Area Thermal Neutron Detectors). Compared with the former CYSP, the sensitivity increased approximately by an order of magnitude. This paper presents CYSP-HS focusing on the new internal detectors, the response matrix and its verification in a reference field of Am-Be available at the Politecnico di Milano. Highlights: A high-sensitivity, single-modetator, directional neutron spectrometer, CYSP-HS, was developed. CYSP-HS is an upgrade of the neutron spectrometer CYSP. Large Area semiconductor-based thermal neutron detectors were used. CYSP-HS and CYSP response matrices were compared. CYSP-HS response matrix was verified in a reference Am-Be field.